Mammary tumor development induces perturbation of liver glucose metabolism with inflammation and fibrosis - Charlot, Anouk; Bringolf, Anthony; Mallard, Joris; Jaulin, Amélie; Crouchet, Emilie; Charles, Anne-Laure; Duteil, Delphine; Alpy, Fabien; Tomasetto, Catherine-Laure; Baumert, Thomas F; Zoll, Joffrey (American journal of physiology: endocrinology and metabolism, 2025)
Cancer cells rely on glycolysis and lactic fermentation for ATP production, inducing an abnormal glucose uptake in tumors. However, it is largely unknown whether the increased tumor glucose consumption affects overall body glucose homeostasis including perturbation of the liver glucose production pathways. The effect of mammary tumor development on the liver metabolism pathway was examined by using a mouse model based on FVB/N wild-type (WT-SD) and FVB/N-Tg(MMTV-PyVT)634Mul/J mice (Tg-SD), who develop spontaneous mammary tumors. Blood and livers were analyzed for metabolic changes, by measuring histological staining, signaling, and insulin sensitivity. Tg-SD mice developed mammary tumors with an average weight of 6 g, and cancer development increased total food intake without impacting body weight gain. Tumor development did not affect blood glycemia and lactate levels but increased insulin and homeostasis model assessment of insulin resistance (HOMA-IR) index ( = 0.06). In the liver, Tg-SD mice with tumors exhibited a decrease in glycogen content and an increase in gluconeogenesis gene expression, as G6pc, Pgc1α, and Foxo1 ( < 0.05), as well as Pepck and Ldha ( < 0.01). Moreover, the phosphorylation of AMPK and AKT was significantly decreased ( < 0.01 and < 0.05, respectively). Surprisingly, liver fibrosis was markedly increased in Tg mice ( < 0.05) alongside elevated inflammatory gene expression, such as IL1β ( < 0.01) or IL6 ( < 0.05). Here, we found that the development of non-metastatic mammary tumors using the MMTV-PyMT mouse model disrupts liver function through the development of inflammation, fibrosis, and metabolic perturbation, including an increase in glucose production and insulin resistance. Finally, these observations unravel a previously unknown metabolic cross talk between the tumors and the liver. This work demonstrates that the spontaneous development of non-metastatic mammary tumors triggers hepatic activation of endogenous glucose production pathways, coinciding with the onset of insulin resistance. This finding suggests a significant cross talk between tumors and the liver during tumorigenesis, aiming at enhancing glucose production to meet the elevated energy demands of the tumor. Understanding this interaction could provide insights into metabolic alterations associated with cancer and lead to potential therapeutic targets to inhibit tumor metabolism.